Role of Cytology in Detection of Unsuspected Carriers of Microfilariae: A Retrospective Study in National Capital Region (NCR), India - Dubey, Suparna; Mishra, Jyoti; Srivastav, Srijan; Goel, Anchit; Gupta, Madhuvan; Deshmukh, Geeta (Annals of Pathology and Laboratory Medicine, 2018)
Background: Filariasis, a global problem, is a major public health issue in India. Despite its high incidence, it is unusual to detect microfilaria in cytological smears, though unexpected detection of microfilariae in fine needle aspiration cytology (FNAC), exfoliative and fluid cytology have been reported previously. The study analyzed the role of cytology in detection of asymptomatic carriers of microfilariae. Methods: This was a retrospective, observational study and included cases of filariasis from cytological records spanning five years. The epidemiological, clinical, hematologic and radiologic details were noted. The slides were retrieved and examined. Descriptive statistical analysis was utilized. Result: Filariasis was diagnosed in 0.03% of the total cytology cases studied during the period, constituting 0.04% of FNACs (two cases of inguino-scrotal swellings, two of breast lumps, one of thyroid swelling) and 0.02% of cervicovaginal smears (two cases). None of them was clinically suspected to be filariasis. Radiological examination was also misleading. None of the cases demonstrated raised leukocytosis or microfilaremia and eosinophilia was present in 3 cases (42.9%). Apart from microfilariae of Wuchereria bancrofti, eggs were present in one case. This was associated with inflammation in all cases, cell adherence in 42.9% and coexistent hyperplastic and neoplastic conditions in 57.1% cases. Conclusion: The detection of microfilariae in cytological material in the absence of clinical, radiologic or hematologic suspicion, in an area of relatively low prevalence of filaria, points to the need for a high index of suspicion and careful screening of all smears, as cytology may play an important role in the diagnosis of asymptomatic carriers of microfilariae. DOI:10.21276/APALM.1727